An improved ant colony optimization for the multi-trip Capacitated Arc Routing Problem. (July 2019) - Tirkolaee, Erfan Babaee; Alinaghian, Mehdi; Hosseinabadi, Ali Asghar Rahmani; Sasi, Mani Bakhshi; Sangaiah, Arun Kumar
Abstract: The urban waste collection problem and its disposal activities are among the most important municipal services involving many operational issues. In this paper, a mixed-integer linear programming (MILP) model was developed for the multi-trip Capacitated Arc Routing Problem (CARP) in order to minimize total cost. In the proposed model, depots and disposal facilities were located in different places. In order to validate the proposed model, several small-sized instances were solved by the CPLEX solver of GAMS software. Then, a hybrid algorithm using the Taguchi parameter design method was developed based on an improved Max-Min Ant System (IMMAS) to solve well-known test problems and large-sized instances. Computational results show high efficiency for the proposed algorithm.